2021
DOI: 10.1007/s11356-021-17749-z
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic rock powder residues as precursors for the synthesis of adsorbents and potential application in the removal of dyes and metals from water

Abstract: The present study verified the potential of volcanic rock powder residues originating from the extraction of semi-precious rocks in the state of Rio Grande do Sul, Brazil, as precursors or adsorbents for dyes and metallic ion removal from water. In this way, it is possible to add value and give an adequate destination to this waste. Volcanic rock powder residues from Ametista do Sul (AME) and Nova Prata (NP) were the starting materials. These were used naturally or submitted to the alkaline activation process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Minerals are a resource that can be found in rocks which are abundant in Indonesia. If processed they will produce metals and various materials needed in industrial processes and have economic value [7]. One of the minerals that is often contained in rocks is the mineral silica (SiO2) ranging from 44.89-47.76% and 71.62%, as it is known that silica is formed from the weathering of rocks that contain main minerals, such as quartz and feldspar.…”
Section: Introductionmentioning
confidence: 99%
“…Minerals are a resource that can be found in rocks which are abundant in Indonesia. If processed they will produce metals and various materials needed in industrial processes and have economic value [7]. One of the minerals that is often contained in rocks is the mineral silica (SiO2) ranging from 44.89-47.76% and 71.62%, as it is known that silica is formed from the weathering of rocks that contain main minerals, such as quartz and feldspar.…”
Section: Introductionmentioning
confidence: 99%
“…The high adsorption efficiency of VR with heavy metals was also proved by assays elsewhere (Alemayehu et al, 2011). A study on the potential use of VR powder as adsorbent for removing dyes and metals from water showed that using VR powder showed better results of removal capacity for all these contaminants from water (Rossatto et al, 2022).…”
Section: Introductionmentioning
confidence: 99%